An analysis of the impact of administrative approval reform on the technological complexity of manufacturing exports - Tingting Jiang; Zhibin Zhang (PLoS ONE, 2025)
As the global economic landscape evolves, the low technological content and persistent lack of international competitiveness in China’s manufacturing exports have become increasingly apparent, underscoring the urgent need for a transition from “quantity” to “quality” in the sector. Administrative approval reform, a key pillar of institutional innovation in the new era, plays a critical role in enhancing the technological complexity of manufacturing exports and strengthening international competitiveness. Using data from 2001 to 2013, this study investigates the impact of administrative approval reform on the technological complexity of manufacturing exports and explores its underlying mechanisms from both theoretical and empirical perspectives. Theoretical model analysis suggests that administrative approval reform effectively increases technological complexity by reducing the marginal and fixed costs associated with adjusting product complexity. Empirical findings provide robust evidence that administrative approval reform significantly enhances technological complexity, with results holding across various sensitivity tests. At the micro level, the reduction of institutional transaction costs emerges as a key channel through which the reform exerts its impact. Additionally, increasing investment in research and development, fixed assets, and technological innovation are identified as critical pathways influencing technological complexity. The reform’s effects are particularly pronounced for non-state-owned enterprises and firms located in coastal and port cities, as revealed by a heterogeneity analysis. Furthermore, a decomposition of city-level export technological complexity using the DOP method shows that improved inter-firm resource allocation—by shifting market share from firms with lower technological complexity to those with higher technological complexity—serves as the primary mechanism driving the observed improvements at the city level. This study contributes to the literature by providing empirical evidence on the role of administrative approval reform in fostering the technological upgrading of manufacturing exports, highlighting its differentiated impact across firm types and regions. The findings offer valuable insights for policymakers seeking to enhance the technological complexity and international competitiveness of manufacturing exports in China.